2015
DOI: 10.1094/phyto-04-14-0106-r
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping of Seedling Resistance to Spot Form Net Blotch in a Worldwide Collection of Barley

Abstract: Spot form net blotch (SFNB), caused by the necrotrophic fungal pathogen Pyrenophora teres f. maculata, is an important foliar disease of barley in major production regions around the world. Deployment of adequate host resistance is challenging because the virulence of P. teres f. maculata is highly variable and characterized minor-effect resistances are typically ineffective against the diverse pathogen populations. A world barley core collection consisting of 2,062 barley accessions of diverse origin and geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 72 publications
6
49
0
Order By: Relevance
“…Tamang et al identified markers at 53.7–59.2 cM (consensus map) on chromosome 4H associated with seedling resistance against the two SFNB isolates NZKF2 and DEN.2 from New Zealand and Denmark, respectively, and this region co-locates with AL_QRptt4-1 found in this study [26]. One of the markers significantly associated with resistance to NZKF2 and DEN2.6 is also present in the AxL linkage map and showed significant association with seedling resistance to 6949B.…”
Section: Discussionsupporting
confidence: 58%
“…Tamang et al identified markers at 53.7–59.2 cM (consensus map) on chromosome 4H associated with seedling resistance against the two SFNB isolates NZKF2 and DEN.2 from New Zealand and Denmark, respectively, and this region co-locates with AL_QRptt4-1 found in this study [26]. One of the markers significantly associated with resistance to NZKF2 and DEN2.6 is also present in the AxL linkage map and showed significant association with seedling resistance to 6949B.…”
Section: Discussionsupporting
confidence: 58%
“…The pathogen exists in two forms based on the symptoms they cause: the net form of net blotch (P. teres f. teres) and the spot form of net blotch (P. teres f. maculata). The net form of net blotch (NFNB) is the dominant form in different regions of Russia; the spot form of net blotch (SFNB) was found only in the southern part of European Russia [1]. NFNB epidemics in Northwest Russia appear with a frequency of 5 times every 10 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, genome-wide association studies (GWAS) have been used to identify genomic regions associated with resistance/susceptibility. Tamang et al (2015) used SFNB disease reaction data ( Neupane et al 2015 ) and genotypic data ( Muñoz-Amatriaín et al 2014 ) from a 1480-line barley core collection to identify 27 distinct loci associated with SFNB resistance/susceptibility. Among the 27 loci identified in GWAS, six loci were consistent with previously identified QTL ( Tamang et al 2015 ).…”
mentioning
confidence: 99%
“… Tamang et al (2015) used SFNB disease reaction data ( Neupane et al 2015 ) and genotypic data ( Muñoz-Amatriaín et al 2014 ) from a 1480-line barley core collection to identify 27 distinct loci associated with SFNB resistance/susceptibility. Among the 27 loci identified in GWAS, six loci were consistent with previously identified QTL ( Tamang et al 2015 ). Similarly, Wang et al (2015) identified 29 marker trait associations (MTA) that represented 24 unique regions among 898 breeding lines from the Northern Region Barley Breeding Program in Australia.…”
mentioning
confidence: 99%